Production of pigments by Monascus ruber CCT0302 in culture media containing maltose as substrate - Oliveira, Camila Fernanda Dias; Cardoso, Lígia Alves da Costa; Vendruscolo, Francielo (Frontiers in Sustainable Food Systems, 2022)
The aim of this study was to show how maltose production residues can be used to obtain natural pigments by Monascus ruber CCT 3802 in solid and submerged cultures. The microbial growth and the colour and heat stability characteristics of the pigments produced in both solid and submerged media, with different maltose syrup concentrations, were determined. The results showed that the addition of maltose provided significant increases in the velocity of microbial growth and production of red pigments. The highest radial growth velocity of Monascus ruber (0.1053 mm h−1) was obtained when cultivated in a medium containing 5 g L−1 of maltose syrup, corresponding to a 71.7% increase in growth as compared to the growth velocity in the control medium. Using submerged fermentation, the culture medium containing 10 g L−1 of maltose syrup provided the greatest concentrations of red pigments (14.54 AU510nm g−1 dry biomass) with an intense dark red colour, showing that Monascus ruber CCT 3802 had the capacity to assimilate the substrate and produce pigments. The red pigments produced in the cultures showed good heat stability with activation energies of 13.735 Kcal mol−1.